PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012 – 2016 - Rizky Wulandari; V. Santi Paramita (Prosiding Working Papers Series In Management, 2018)
This study aims to determine the direct effect of profitability proxied by ROA and ROE, and the capital structure proxied by DER to stock prices and the indirect influence of ROA and ROE on stock prices through the capital structure of property & real estate firms listed on the Indonesia Stock Exchange the period 2012-2016. Sampling technique using purposive sampling obtained as many as 20 companies, the method of data analysis using descriptive analysis, multiple regression analysis is extended with path analysis. The result of the research shows that ROA have a significant negative effect to capital structure, ROE has positive significant effect to capital structure, ROA and ROE has no significant effect on stock price, DER has significant negative effect to stock price, ROA and ROE have indirect effect to share price through capital structure as intervening variable. Keywords: Return on Asset, Return on Equity, Debt to Equity Ratio, Price Stock.